Bedside temporary transvenous cardiac pacing lead placement in patients with tricuspid valve surgery without guidance of X‐ray: A single‐center experience. Issue 6 (14th September 2022) - Chen, Mingxian; Wang, Zhuo; Wang, Songyun; Zhu, Tongjian; Liu, Zhenjiang; Li, Xuping; Wu, Zhihong; Liu, Qiming; Zhou, Shenghua
Abstract: Background: It is difficult to insert cardiac pacing leads in patient with tricuspid valve surgery (TVS). The aim of this study was to evaluate safety and effectiveness of a novel technique applied for bedside temporary pacemaker placement (TPP) in patients with TVS. Methods: We investigated patients with TVS who required bedside TPP without X‐ray guidance in cardiac intensive care unit between January 2019 and March 2022. They were divided into Novel pre‐shaped group ( N = 21) and Control group (routine pre‐shaped group, N = 26). The ordinary bipolar electrodes were applied in both groups. In Novel pre‐shaped group, electrodes were reshaped by a novel technique with three‐curve with anterior tip method, while electrodes were shaped by traditional strategy in Control group. We evaluated the operation duration, first‐attempt success rate of the lead placement, pacing threshold, success rate of lead placement, the rate of leads displacement, and complications. Results: Compared with that in Control group, the procedure time was significantly shortened and the first‐attempt success rate of lead placement was obviously increased in Novel pre‐shaped group (both p < 0.05). Although there was a slight reduction in complications in Novel pre‐shaped group when compared with that in Control group. However, there were no statistical significance in pacing threshold, the success rate of lead placement, the rate of leads displacement, and complications when compared between two groups. Conclusions: We propose a novel technique, three‐curve with anterior tip method, is a feasible and effective bedside method to insert emergency temporary pacing leads in patients with TVS. Abstract : Tricuspid valve surgery (TVS) is associated with a high risk of AVB III required temporary pacemaker placement (TPP) for emergency protection. However, it is difficult to insert pacing leads because of the deformation of tricuspid annulus. The aim of this study was to evaluate the safety and effectiveness of a novel technique applied for bedside TPP in patients with TVS. Herein, we propose a novel technique, three‐curve‐tip‐anterior toward method, is a feasible and effective bedside method to insert emergency temporary pacing leads in patients with TVS.